Impact of cognitive behavior therapy on osteoarthritis-associated pain, insomnia, depression, fatigue, and physical function in patients with knee/hip osteoarthritis: A systematic review and meta-analysis of randomized controlled trials - Lin, Hong-Min; Hsieh, Pei-Shan; Chen, Nai-Ching; Tsai, Chiung-Huei; Kuo, Wen-Fu; Lee, Ying-Li; Hung, Kuo-Chuan (Frontiers in Medicine, 2023)
Background: This meta-analysis aimed at evaluating the efficacy of cognitive behavior therapy (CBT) against osteoarthritis-associated symptoms in patients with knee/hip osteoarthritis. Methods: Medline, PubMed, Cochrane Library, and EMBASE databases were searched from inception to July 2022 to identify randomized controlled studies (RCTs) comparing the efficacy of CBT with other treatment approaches in adults with confirmed knee/hip osteoarthritis. The pain intensity (primary outcome) and the secondary outcomes including insomnia severity, sleep efficiency, physical function as well as the severity of depression and fatigue were assessed at two time points (i.e., immediately after treatment and during the follow-up period). The effect size is expressed as standardized mean difference (SMD) with SMDs of <0.2, 0.2-0.5, and 0.5-0.8, and >0.8 representing negligible, small, medium, and large effect sizes, respectively. Results: Fifteen RCTs were included for analysis. Immediately after CBT intervention, meta-analysis showed similar treatment effect in pain severity [SMD=-0.46, 95% confidence interval (CI): -0.95 to 0.04, 11 studies, 1557 participants] and other symptoms including depression (SMD=-0.26, 95% CI: -0.58 to 0.06, five studies, 735 participants), fatigue (SMD=-2.44, 95% CI:-6.53 to1.65, two RCTs, 511 participants), and physical function (SMD=-0.11, 95% CI:-0.25 to 0.02, five RCTs, 720 participants) between CBT and control groups, while there was an improvement in insomnia severity (SMD=-0.65, 95% CI: -1.06 to -0.24, four RCTs, 639 participants, medium treatment effect) and sleep efficiency (SMD=0.32, 95% CI: 0.04 to 0.59, three RCTs, 352 patients, small treatment effect). During follow-up, CBT improved pain severity (SMD=-0.52, 95% CI: -1.03 to -0.01, eight studies, 1447 participants, medium treatment effect), insomnia (SMD=-0.43, 95% CI: -0.85 to -0.01, three RCTs, 571 participants, small treatment effect), and depression (SMD=-0.39, 95% CI: -0.59 to -0.18, four RCTs, 791 participants, small treatment effect). Nevertheless, sleep efficiency, fatigue, and physical function were not improved in the follow-up period. Conclusion: Our results may suggest the durability of CBT-associated treatment benefits, supporting its role as a potential promising alternative or complementary intervention for patients with knee/hip osteoarthritis, especially against pain and insomnia. Future large-scale investigations are warranted to verify our findings.